Fundamentals, misvaluation, and investment: the real story - Robert S. Chirinko; Huntley Schaller (Center for Economic Studies and ifo Institute (CESifo), 2007)
Is real investment fully determined by fundamentals or is it sometimes affected by stock market misvaluation? We introduce three new tests that: measure the reaction of investment to sales shocks for firms that may be overvalued; use Fama-MacBeth regressions to determine whether overinvestment affects subsequent returns; and analyze the time path of the marginal product of capital in reaction to fundamental and misvaluation shocks. Besides these qualitative tests, we introduce a measure of misvaluation into standard investment equations to estimate the quantitative effect of misvaluation on investment. Overall, the evidence suggests that both fundamental and misvaluation shocks affect investment.
Keywords: E44; E22; E32; G3; 330; Kapitalanlage; Börsenkurs; Wertpapieranalyse; Schock; Schätzung; USA